Visual‐based autonomous field of view control of laparoscope with safety‐RCM constraints for semi‐autonomous surgery. Issue 2 (20th February 2020) - Sun, Yanwen; Pan, Bo; Fu, Yili; Niu, Guojun
Abstract: Purpose: The surgeon is not timely in direct control of his field of view. Autonomous laparoscope control can provide appropriate surgical field of view and facilitate the intelligent level of surgical robot system. Methods: This study explores an autonomous laparoscope control framework for semiautonomous surgery. We propose a novel concept that integrates two forms of Remote Center of Motion (RCM) constraint. We also propose a novel safety‐RCM model to cope with the collision condition. We modify the image Jacobian matrix to realize RCM constraint. The two models constitute a dual‐RCM constraint for robot laparoscope arm. We perform validation of the algorithm with two experiments. Results: The experimental results show that the RCM position error can be reduced with the dual‐RCM constraint. Owing to safety‐RCM model, autonomous surgical field of view control could still be realized in case of collision. Conclusion: The autonomous laparoscope control could be realized with safety‐RCM and dual‐RCM algorithms.